SISTEM CERDAS KONTROL MATA AIR DEMI KELANGSUNGAN KEGIATAN MASYARAKAT DI KASEPUHAN SINAR RESMI - Dudih Gustian; Marina Artiyasa; Muahamad Taufik; Nuraeni; Yudi Nata (Bahasa Indonesia, 2022)
One of the areas included in the global scope of the geopark is culture, where the culture is included from the characteristics of an area which certainly gives value to the point of Recognition of UNESCO. One of the sacred areas that is quite well known and upholds the traditions of its ancestors is the Official Ray.But there is a problem is that there is a queue of residents to get clean water that has been flowed to several public toilets in kasepuhan. But if the available public toilets are full, then residents are forced to take water from public toilets that are located close to the spring. Sometimes the water that comes from the springs that have been used by the community does not always flow well, but sometimes it is choked during the dry season. On the other hand, other springs are quite good and are predicted to always be available even during the dry season to supply the needs of the community is quite far from the location of the cascade. This certainly results in people having difficulty in meeting hygiene needs for daily activities. This PKM activity provides a solution by building a spring drainage system that is able to produce vacuum pump performance that can be monitored with android applications so that it can always be controlled performance. It is hoped that this activity can help the community of the official sinar kasepuhan in meeting the needs of clean water in daily activities. Abstrak Salah satu kawasan yang termasuk dalam scope global geopark ialah budaya, yang mana budaya itu masuk dari ciri khas dari suatu daerah yang tentunya memberi nilai point pengakuan UNESCO. Salah satu kawasan kesepuhan yang cukup dikenal dan memegang teguh tradisi para leluhurnya ialah Sinar Resmi.Namun terdapat permasalahan ialah adanya antrian warga untuk mendapat air bersih yang telah dialirkan ke beberapa wc umum yang ada di kasepuhan. Tetapi jika wc umum yang tersedia penuh, maka warga terpaksa mengambil air dari wc umum yang lokasinya dekat dengan sumber mata air. Selin itu terkadang air yang berasal dari sumber mata air yang selama ini digunakan masyarakat tidak selamanya mengalir dengan baik, tetapi terkadang tersendat saat musim kemarau. Dilain sisi sumber mata air lainnya yang cukup baik dan diprediksi selalu tersedia meski saat musim kemarau untuk mensuplay kebutuhan masyarakat berjarak cukup jauh dari lokasi kasepuhan. Hal ini tentu mengakibatkan masyarakat kesulitan dalam memenuhi kebutuhan kebersihan untuk aktifitas keseharian. Kegiatan PKM ini memberikan solusi dengan membangun sistem pengotrolan mata air yang mampu menghasilkan kinerja pompa vacuum yang dapat dipantau dengan aplikasi Android sehingga dapat selalu terkontrol kinerjanya. Diharapkan kegiatan ini dapat membantu masyarakat pihak kasepuhan sinar resmi dalam memenuhi kebutuhan air bersih dalam kegiatan keseharian.